Efficacy of Antagonistic Bacillus spp. Isolates on Growth Promotion of Musa (ABB group) ‘Kluai Hin’ and Vermicompost Granule Production - Laopha, Akkachai; Ponphang-nga, Pancheewan; Rattanapolsan, Ladawan; Kawicha, Praphat; Sangdee, Aphidech; Arjcharoen Theanhom, Araya; Wongmaneeroj, Monthar; Homhual, Rongrong (Thai Journal of Science and Technology, 2021)
The objective of this research was to study the ability of Bacillus spp. isolate JK62, JK106, KB1-2 B4, JK127, JK74, YH3-2 B2, and YH3-2 B4 to promote the growth of Musa (ABB group) ‘Kluai Hin’ under greenhouse conditions and produce vermicompost granule. At a concentration of 108 CFU/ml, Bacillus spp. isolates were used to soak roots of 1-month-old micro-propagated ‘Kluai Hin’. After five weeks of transplanting, the results showed that the Bacillus spp. isolate JK74 and YH3-2B2 significantly promoted the height of the test plants, but there were no significant differences in fresh and dry weight compared to the control treatments. Bacillus spp. isolates JK74, YH3-2B2, and JK106 were used to produce vermicompost granule formula V+JK74, V+YH3-2B2, and V+JK106. Sporulating Bacillus spp. cells were enriched in vermicompost by spraying during the crushing and granulating process and after the granulating process. The fertilizers were mixed in the planting material and used to grow a 1-month-old micro-propagated banana. After seven weeks of transplanting, it was found that all Bacillus spp.-enriched vermicompost granules significantly increased the height of the test plants compared with other treatments. The formula V+JK106 and V+JK74 significantly increased the fresh weight of the test plants compared to formula V (non-Bacillus enriched vermicompost granule), but there were no significant differences in dry weight.